Amperometric detection of nitric oxide using a glassy carbon electrode modified with gold nanoparticles incorporated into a nanohybrid composed of reduced graphene oxide and Nafion - Yusoff, N.; Rameshkumar, P.; Shahid, M.M.; Huang, S.T.; Huang, N.M. (Springer Verlag (Germany), 2017)
The authors show that the electrocatalytic performance toward the detection of nitric oxide (NO) can be enhanced by making use of gold nanoparticles (AuNP) in a matrix consisting of reduced graphene oxide and Nafion (rGO-Nf). The rGO-Nf@Au nanohybrid was synthesized via a hydrothermal method. The spherical AuNP have diameters in the range from 50 to 200 nm as proven by field emission scanning electron microscopy (FESEM). A glassy carbon electrode (GCE) modified with the nanohybrid displays excellent electrocatalytic activity towards NO oxidation compared to other kinds of modified electrodes. Best operated at a voltage of +0.8 V (vs. SCE), the amperometric response was linear in the 1 μM to 0.16 mM nitrite concentration range, with 0.5 μM detection limit (at an S/N ratio of 3). The high surface area of the AuNP along with the synergistic effect of AuNP and rGO-Nf film on the signal current is believed to cause the enhanced electrocatalytic activity of the nanohybrid. The sensor is not interfered by dopamine (DA), ascorbic acid (AA), uric acid (UA), glucose, urea, and NaCl even in 5-fold higher concentrations. In our perception, the rGO-Nf@Au modified electrode is a promising tool for highly sensitive and selective amperometric sensing of NO.